O nowy model podręczników szkolnych = A New Model for Textbooks - Bortnowski, Stanisław (Zielona Góra: Lubuskie Towarzystwo Naukowe)
At the outset the author reminds that the evolution of modern didactics objects to give ready information to pupils and tends towards problem methods, whereas literature textbooks are written traditionally. They are characterized by:
Keywords: dydaktyka literatury; podręczniki